2015
DOI: 10.1111/jiec.12360
|View full text |Cite
|
Sign up to set email alerts
|

Modular Upgradability in Consumer Electronics: Economic and Environmental Implications

Abstract: SummaryModularly upgradable product designs have been advocated to offer environmental and economic advantages; however, they are not commonly used in the consumer electronics industry. In this article, we investigate the economic and environmental benefits and challenges of modular upgradability for consumer electronics. From an economic point of view, we posit that the limited adoption of modular upgradability in consumer electronics is owing to various demand-, technology-, and competition-related issues. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…This exemplifies the speculated environmental benefits of smart factories as a more efficient manufacturing paradigm (Radziwon et al, 2014). Specifically, the manufacturing processes of outsourced modules at suppliers also show higher energy efficiency, compared with corresponding manufacturing processes in Haier (see Tables S7 and S8 is not in the "optimal" state from the view of procurement, as it may not necessarily lead to superior environmental performance (Agrawal, Atasu, & Ülkü, 2016;Yang, Yu, & Jiang, 2014). For the refrigerator delivery, the values of all categories are increased by about 4.00%, which can be attributed to the increased transportation mileages, because each refrigerator is supposed to be delivered to its customer directly.…”
Section: Analysis Of Hot Spotsmentioning
confidence: 74%
See 1 more Smart Citation
“…This exemplifies the speculated environmental benefits of smart factories as a more efficient manufacturing paradigm (Radziwon et al, 2014). Specifically, the manufacturing processes of outsourced modules at suppliers also show higher energy efficiency, compared with corresponding manufacturing processes in Haier (see Tables S7 and S8 is not in the "optimal" state from the view of procurement, as it may not necessarily lead to superior environmental performance (Agrawal, Atasu, & Ülkü, 2016;Yang, Yu, & Jiang, 2014). For the refrigerator delivery, the values of all categories are increased by about 4.00%, which can be attributed to the increased transportation mileages, because each refrigerator is supposed to be delivered to its customer directly.…”
Section: Analysis Of Hot Spotsmentioning
confidence: 74%
“…The increases of the values of most impact categories are about 12.70%. Notably, the current product modularity is not in the “optimal” state from the view of procurement, as it may not necessarily lead to superior environmental performance (Agrawal, Atasu, & Ülkü, ; Yang, Yu, & Jiang, ). For the refrigerator delivery, the values of all categories are increased by about 4.00%, which can be attributed to the increased transportation mileages, because each refrigerator is supposed to be delivered to its customer directly.…”
Section: Resultsmentioning
confidence: 99%
“…More durable products may require more and/or higher quality material and for active products the use life efficiency versus benefits of use extension comes into play. There is also a risk that products with a modular design are needlessly upgraded (Agrawal et al, 2016).…”
Section: Guidelines -What Measures Suit What Kind Of Product?mentioning
confidence: 99%
“…Bellezza et al (2017) found that consumers are more careless with their possessions if they know an upgrade is available. Relatedly, the limited market success of modular phones or phones that are specifically optimized to allow unlimited repair and upgrades (e.g., Fairphone) challenges the notion that repairability is a highly sought-after feature in smartphones (Lowe 2016;Agrawal et al 2016;Hill 2017). Thus, despite growing advocacy and pending legislation affirming consumers' "right to repair" (The Repair Association 2017; Koebler 2017; Bloomberg 2017), it remains unclear whether consumers truly value the ability to repair and upgrade devices and to what extent such enhanced functional durability (defined here as the duration of time products remain functionally up to date) extends the use phase in smartphones.…”
Section: Repairability and Intangiblesmentioning
confidence: 99%